Crisis leadership during COVID-19: the response of ASEAN and EU regional leaders - Loi, Nguyen; Oleksandr, Tkachenko; Oliver, Crocco; Victoria, Jonathan (Taylor & Francis, 2022)
The COVID-19 pandemic has tested the leadership in organizations of all sizes, industries, and geographic areas. Although substantive literature exists on leadership during a crisis, less attention has been paid to regional leadership and leaders’ response during a crisis. The critical roles that regional organizations such as the Association of Southeast Asian Nations (ASEAN) and the European Union (EU) play in a crisis call for a better understanding of how these organizations and their leaders respond to regional crises. This paper provides a comparative insight into regional leaders’ crisis leadership and communication approaches in ASEAN and the EU during the COVID-19 pandemic in 2020. We describe the response timelines of the two regional organizations and highlight the significant roles of regional leaders in coordinating and implementing regional responses during a crisis, including providing consistent communication and collective leadership to facilitate cooperation, solidarity, and efforts towards recovery. We provide implications for HRD research and practice, specifically around the role of regional leaders in creating and implementing Regional HRD mechanisms in response to crises.